Development of Normalized Cdna Library from Fusarium Wilt Infected Roots of a Tolerant Banana Genotype 'Calcutta-4' Musa acuminata ssp. burmannicoides - V Swarupa (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Management of the most devasting disease, Fusarium wilt of banana, caused by the fungus Fusarium oxysporum f. sp., cubense, is a challenge to the plant pathologist and the banana grower. Currently, genomics is providing the way for understanding plant defense mechanism, having acquired an important place in crop improvement. To identify the relevant genes and to understand the defense mechanism induced during Fusarium wilt infection, a normalized cDNA library was constructed from infected root samples of a tolerant banana genotype, Musa acuminata spp. burmannicoides 'Calcutta-4', by duplex specific nuclease (DSN) based normalization, using the SMART (switching mechanism at 5' end of RNA transcript) full-length cDNA construction method. Sequencing and analysis of 600 clones revealed 392 non-redundant clones. In all, of 88% of the sequences were annotated using Musa genome database, and the remaining 12% were identified as novel loci not annotated. We observed several resistance genes, ROS scavenging genes and genes involved in ubiquitin-proteosome pathway in this study. These genes may have a possible role against Foc infection. These sequences would enrich the EST data developed against specific stress, which is an indispensable tool for predicting functional genes and understanding the defense mechanism.